2015
DOI: 10.1080/00140139.2015.1058426
|View full text |Cite
|
Sign up to set email alerts
|

Sleep and need for recovery in shift workers: do chronotype and age matter?

Abstract: Chronotype seems to better explain individual differences in sleep than age. In view of ageing societies, it might therefore be worthwhile to further examine the application of chronotype for individualised shift work schedules to facilitate healthy and sustainable employment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(31 citation statements)
references
References 50 publications
(53 reference statements)
2
26
1
Order By: Relevance
“…van de Ven et al. 47 ) found similar results among rotating shift workers in the industrial sector in the Netherlands. Workers who had a chronotype that did not align with the shift worked had shorter sleep duration, quality, and longer time for recovery.…”
Section: Resultsmentioning
confidence: 58%
See 1 more Smart Citation
“…van de Ven et al. 47 ) found similar results among rotating shift workers in the industrial sector in the Netherlands. Workers who had a chronotype that did not align with the shift worked had shorter sleep duration, quality, and longer time for recovery.…”
Section: Resultsmentioning
confidence: 58%
“…Further support in the relationship of matching chronotype to shift timing was found in the studies focused on sleep characteristics 20 , 45 , 47 , 48 , 49 ) . The research strongly supported chronotype misaligned with shift timing was associated with decreased sleep duration and quality 20 , 48 ) .…”
Section: Discussionmentioning
confidence: 78%
“…A similar finding is derived in Blok and de Looze's (2011) literature review; although some differences between older and younger workers are reported, it is concluded that there is no evidence of more shift work problems among older workers. In contrast, Van de Ven et al (2016) found that older shift workers report shorter sleep duration, more disturbed sleep and more complaints on waking up.…”
Section: Analysis and Evaluation Of Ageing Workers' Functional Capacimentioning
confidence: 77%
“…A chronotype strongly correlates with the quality of nighttime sleep. One study indicated that chronotypes more comprehensively explain individual differences in nocturnal sleep than does age [ 16 ]. Children of evening type had shorter nocturnal sleep times during weekdays than did other children [ 17 ].…”
Section: Introductionmentioning
confidence: 99%